Differential sensitivity of Ustilago maydis to fungal antibiotics on simple and complex media - Anju Verma; Tamas Kapros; Jakob H. Waterborg (Fungal Genetics Reports, 2016)
We have observed that the basidiomycete Ustilago maydis can be partially or completely resistant to antibiotics when grown in defined growth media. In synthetic medium based on the fully defined mixture of simple organic compounds and salts U. maydis displays near wild-type growth at concentrations of hygromycin that effectively kill cells in complex nutrient media. The antibiotics geneticin, nourseothricin and phleomycin had similar effects. In contrast, the fungicide carboxin was equally effective in all growth media tested. Our observations could guide selection of growth media for genetic transformation of Ustilago and other fungi when sensitivity to common antibiotics is used as a selectable marker.